Economic Analysis of the Impacts of Building E-Government Passport and Traffic Directorates in Sulaymaniyah Governorate in the Kurdistan Region of Iraq as a Case Study - Khalid Haider Abdul Ali; Chenar Asaad Mohammed Abdullah (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Many countries of the world have benefited from the phenomenon of globalization in transforming their traditional governments into e-government and benefiting from it by raising the efficiency of performance, reducing public expenditure and seeking to deliver their societies to prosperity. It is therefore important to state the effects of e-government on various aspects of life in general and economic in particular which will be addressed as the subject of this research, where through the application of e-government, the use of information technology, and communication through the financial resources, administrative and legal available in the achievement of economic and social welfare. Therefore, based on the latter, it will be sought to indicate how the Kurdistan Regional Government of Iraq benefited from the transfer, through the taking of two examples for verification, namely the directorates of passports and traffic in the province of Sulaymaniyah.